Intuition in decision making - Risk and opportunity. (18th August 2020) - Adam, Frederic; Dempsey, Eugene
ABSTRACT: The role of intuition in decision making has been extensively researched and the body of research which has explored human decision making is vast and complex. Some researchers have remarked that managers rarely have the luxury of basing their decisions on orderly rational analysis and depend on intuition and judgement. To research the role of intuition and capture how to best harness it, we applied a Naturalistic approach in a retrospective case of decision making by an expert neonatologist. We review the tangible and objective elements available when key decisions had to be made and analysed the role of reasoning, judgement and intuition. Our results indicate that the delivery room is a space where experts must still rely on ad-hoc decision-making processes and where subjectivity is very present. IT could be used to promote evidence-based decision making, but expert intuition remains essential.